AN EXAMINATION OF PHYSICAL EDUCATION TEACHERS’ ATHLETE IDENTITY AND SOCIAL MEDIA ADDICTION LEVELS - Akyüz, Onur; Çembertaş, Erhan; Dalay, Yalçın; Bulut, Mustafa; Serçek, Sadık (Veredas do Direito, 2026)
This learning objective is to examine the impact of physical education on social media and athlete performance. A total of 232 physical education teachers, 124 female and 108 male, participated in the study. The "Athlete Identity Scale (ASIS)," adapted for the Turkish session by Öztürk and Koca (2013), was used to determine the level of athlete structure, and the "Social Media Addiction Scale (SMAS)" prepared by Tutgun-Ünal and Deniz (2015) was used to determine the level of social media addiction. The study data were tested using the SPSS 25.0 package program. T-test, One Way ANOVA, and Tukey tests were used. Participation in women's physical education is higher in the amount of social media compared to men's, while men's physical education has a higher social identity level, the intensity of emotional situations in physical education is higher, athletes are more likely to participate in physical education, the amount of physical education in parts is higher, and youth physical education has more social media use (p<0.05). Consequently, social media addiction in physical education is moderate, while athlete performance is high. Furthermore, it has been determined that changes in social media in the organization of physical education vary according to gender and age variables; the athlete's status, exercise status, and educational status vary depending on the variability.